Reações à histoplasmina e paracoccidioidina na Serra de Pereiro (estado do Ceará-Brasil) Hypersensitivity to histoplasmin and paracoccidioidin in people living in Pereiro, Ceará, Brazil - M. J. N. Diógenes; H. M. G. Gonçalves; A. C. P. Mapurunga; K. F. Alencar; F. B. Andrade; J. A. Nogueira-Queiroz (Revista do Instituto de Medicina Tropical de São Paulo, 1990)
Foram realizados 138 testes com histoplasmina e paracoccidioidina no Município de Pereiro - Ceará, obtendo-se positividade de 61,5% e 32,1% respectivamente, a estes antígenos. Os autores discutem a possibilidade da coexistência da histoplasmose e paracoccidioidomicose-infecção e/ou doença na região. Intradermal tests using histoplasmin and paracoccidioidin antigens were performed in 138 persons from Pereiro, Ceará, Brazil. The results were positive in 61.5% and 32.5% with histoplasmin and paracoccidioidin antigens respectively. These results suggest infection by H. capsulatum and P. brasiliensis in the people living in the studied area. New studies are necessary to detect histoplasmosis and paracoccidioidomycosis as clinical diseases in that region.